Assessing the impact of computer use on landscape architecture professional practice: efficiency, effectiveness, and design creativity - Tai, Lolly (The University of Edinburgh, 2001)
Landscape architects claim that computers are efficient and effective presentation tools. However, to date, no one has evaluated the impact of computer use on the nature and quality of design in a practice setting. To further explore this issue, a trial was conducted with landscape architecture students in which they worked in conventional, mixed and digital media. Results indicated that although computer use was efficient in some tasks, the nature of the design process did not yield itself effectively yet to complete computerization. In addition, to assess the impact of computer use more broadly on office practice today, a survey was conducted of over 100 Chapter Executive Members of the American Society of Landscape Architects in the United States of America.

Survey results indicated that computer use has permeated all areas of landscape architecture practice, and that it has genuinely improved drawing quality and capability. However, it has not significantly impacted the artistic or creative aspects. Few respondents believed the computer can improve these facets of the profession or that traditional practice methods will be totally replaced by the computer.

The results suggest that academic and professional sectors of landscape architecture must help educate existing professionals to fully grasp the benefits of current and emerging computer technologies and to prepare the future professionals for an increasingly digital practice.